Drive system of a Linear Switched reluctance Motor Using Microcontroller (Journal of Hama University, 2019)
In this article, we present a study, modeling and simulation of a linear switched reluctance motor LSRM, as well as a presentation of the experimental results comparing with the simulation results to control the speed and position of the three-phase LSRM motor witch have the following spe cifications: 4/6 poles, 24V, 250W, 250N. In the experimental study and simulation, reference velocity is constant depending on the position and the time. The velocity of the moving part is controlled by FLC and PI control methods.The PIC18F452 microcontroller was used because of its low cost for controlling the motor velocity according to the PI control technology. The results were compared with the simulation results of the motor velocity using the FLC method. We proved that the PIC18F452 microcontroller was sufficient to control the velocity of the LSRM motor. We are also investigating that the response of velocity in the FLC method were better than in the PI method concernment the response of velocity and the precision of position. So that it’s preferred for applications that require fast response and accuracy in as medical applications and elevators systems.